Strategi Peningkatan Mutu Pelayanan Kesehatan di Unit Rawat Jalan Poli Jantung di RSUD Kota Kendari Tahun 2024 - Sitti Syaqinah Rahmatiah MZ; Hartati Bahar; Sri Tungga Dewi (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
The level of healthcare quality is determined by the extent to which societal or individual requirements for healthcare are met in alignment with high professional benchmarks, while ensuring prudent resource utilization and impact within government and societal constraints. In addition, it must be delivered in a safe and satisfactory manner to patients, following ethical standards and best practices. Quality indicators of health services in hospitals have challenges in improving the overall quality of health services. In the Cardiac Poly Outpatient Unit at Kendari City Hospital, it is necessary to know the strategies used in improving service quality. The purpose of this study is to ascertain the Strategy for Improving the Quality of Health Services in the Cardiac Poly Outpatient Unit at Kendari City Hospital in 2024. The research methodology used is qualitative and descriptive, using the Phenomenal model to investigate various phenomena in Kendari City Hospital with data collection techniques, namely field observations at the research location and also in-depth interviews with informants who have been determined. The results showed that the quality strategy of health services provided by the Kendari City Hospital is quite good, especially in the Cardiac Poly Outpatient Unit. However, considering the importance of health services, it must always be improved so that the quality of health services received by the community is always maintained. There are still many things that must be considered, for example, the problem of waiting rooms that must be added to the seats for visitors and the speed of service that must still be improved.